Viability of Supercritical Mixtures in Brayton Cycles Coupled to Concentrated Solar Power Plants (Innovation & Development in Engineering and Applied Science, 2021)
In this work it is promoted to study the viability of the use of mixtures based on supercritical CO2 that can lead to thermal yields in Brayton cycles higher than those obtained with the standard fluid (pure s-CO2). The recommended settings to analyze are Recompression and Recompression with intercooling in the main compressor, which may include more than one superheat. These configurations are very transcendental because in terms of efficiency they are the ones with the highest values and, in addition, their total costs per net installed capacity are the lowest compared to other configurations.
Keywords: Supercritical CO2; Concentrated solar power; solar thermal energy plant; binary mixtures